2019
DOI: 10.1097/brs.0000000000002892
|View full text |Cite
|
Sign up to set email alerts
|

Closed Wound Subfascial Suction Drainage in Posterior Fusion Surgery for Adolescent Idiopathic Scoliosis

Abstract: Study Design. A prospective randomized control study. Objective. The aim of this study was to compare the complication rate in adolescent idiopathic scoliosis (AIS) posterior spinal fusion (PSF) surgery with and without drainage. Summary of Background Data. PSF is the mainstay of surgical treatment for AIS. Drains are commonly used despite contradictory findings in the literature for their having any clear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…None of the investigations found a longer length of stay or increased costs in the no-drain collective [26,34,37]. On the contrary, one investigation by Adogwa et al on patients treated with spinal decompression and fusion found a significantly longer length of hospital stay for the drain-use cohort compared to the no-drain cohort (5.0 vs. 2.8 days, p < 0.0001) [18].…”
Section: Impact On Costs and Hospital Staymentioning
confidence: 95%
See 3 more Smart Citations
“…None of the investigations found a longer length of stay or increased costs in the no-drain collective [26,34,37]. On the contrary, one investigation by Adogwa et al on patients treated with spinal decompression and fusion found a significantly longer length of hospital stay for the drain-use cohort compared to the no-drain cohort (5.0 vs. 2.8 days, p < 0.0001) [18].…”
Section: Impact On Costs and Hospital Staymentioning
confidence: 95%
“…In addition, there are two further prospective, randomised studies indicating that drains have no impact on wound healing. Ovadia et al showed that the number of wound healing complications was similar in the study and control groups [26]. Furthermore, Gubin et al performed an open label randomised control trial with a total of 155 patients.…”
Section: Impact On Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Drains are also used across surgical specialties because they are thought to reduce risk of SSI 16 . Ovadia et al [16] showed that drains did not lower wound complication or infection rate after surgical correction of AIS [2]. Kochai and Erkorkmaz [14] showed similar results.…”
Section: Discussionmentioning
confidence: 99%